Dinamika Pemikiran Hukum Islam: Corak dan Karakteristik - Zulkarnain Suleman (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2016)
This paper descibes the dynamic of Islamic law. Dynamics of Islamic law was born through a progressive process of ijtihad. Ijtihad progressive Islamic law gave birth to four products, namely fiqh, fatwa, legislation in Muslim countries (Qanun) and a court decision (making up). The fourth product of the Islamic legal thought is rich with a diverse opinion (deviation). In the Sunni Jurisprudence born five popular Islamic school of thought (Hanafi, Maliki, Shafi'i, Hanbali and Zahiri) with different patterns of thought. Rational Hanafi, Maliki tend to the opinion of the People of Madinah, the moderate Shafii, Hanbali tradition emphasizes the meaning of birth and textual Zahiri.